Autophagy and Mitochondrial Homeostasis During Infection: A Double-Edged Sword - Wang, Sutian; Zhang, Kunli; Yao, Yuchang; Li, Jianhao (Frontiers in Cell and Developmental Biology, 2021)
Autophagy, as an essential biological process that affects immunity, is a powerful tool that host cells use to defend against pathogenic microorganisms infection. Autophagy not only can initiate innate immune responses but degrade the cellular components which provide the conditions for clear the invaders. However, hyperactivated or inhibited autophagy leads to mitochondrial dysfunction that is harmful to body and is involved in many courses of diseases. Mitochondria perform the functions of biological oxidation and energy exchange. In addition, mitochondrion is closely related to cell death, oxygen radical formation and disease. Accumulation of Mitochondrial metabolites affects survival of intracellular pathogens. In this mini review, we focus on the crosstalk between autophagy and mitochondrial homeostasis during infection.